Political Relations of Australia with the United States: 2000–2017 - Sprengel, Mieczysław (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
Relations between Australia and the United States have developed for long time notably during World War II. Over the following decades, cooperation has become more intense as Australians adopt many cultural patterns from the Americans. Australia declared and supported US presidents in military operations, which is why some have called Australia, America’s sheriff for working to stabilize this part of the world. One cannot overlook the personal arrangements between leaders that help shape the dynamic of deepening the mutual relations these two nations. Donald Trump’s personal interactions’ with the Prime Ministers of Australia play a significant role in this regard.